Fisiographic survey of the high courses of hydrographic sub-basins in the crystaline massif of Meruoca, state of Ceará - LIMA, Ernane Cortez; Oliveira, Ulisses da Costa (Geografares, 2021)
This study presents a physiographic survey of the high courses of watersheds and sub-basins inserted in the Meruoca Massif, located in the Northwest region of the State of Ceará. The geoenvironmental system was addressed by digital processing of satellite images landsat 8, and fieldwork. The geosystemic model was used, from which it was defined the existence of a geosystem and eleven geofacies, each geofacies representing one of the sub-basins studied.  The geosystemic research allowed identifying the existence of different environments to leeward and windward of the massif, in term of soils, forms, vegetation cover and fluvial incision. It was also identified that most of the rivers are of the intermittent type, forming rivers of 1st, 2nd and 3rd orders. The conclusion is that the geosystem is fragile and vulnerable to the uses and occupations that have been suffering, which implies risks of high environmental degradation.
Keywords: water resources; Geosystem; Drainage; Environmental analysis; Meruoca Massif